Kazuo Ishiguro’s Idiostyle (Novel “Klara and the Sun”) - G. I. Lushnikova; T. Yu. Osadchaya (Научный диалог)
Interpretations of the multidimensional concept of “writer’s idiostyle” are presented in the framework of the study of its various characteristics, in particular, in the context of the study of a linguistic personality, from the point of view of the linguotypology of a literary text, from the standpoint of a communicative-activity approach. The relevance of studying the idiostyle of a particular author is due to the fact that its characteristic features and original ways of implementing the author’s intention are the most important elements of the characterization of the literary process in a certain era. The novelty of the study is seen in the fact that the new novel by the British writer of Japanese origin K. Ishiguro “Klara and the Sun” has not yet become the subject of study by literary critics. Particular attention is paid to the international aspect, which occupies a leading position in his work. The implementation of such key elements of the writer's idiostyle as genre form, type of narration, chronotope, images of characters, ideological and thematic component, leading stylistic means is analyzed. They are compared with the characteristic features of other works of the author. It is shown that in the novel “Klara and the Sun” literary devices typical for Kazuo Ishiguro’s work continue to develop, however, they receive new development and original implementation, the author’s tasks are solved in a new way, the system of images and interpretation of the main themes and ideas are built in a slightly different way.